Principles of economics - Case, Karl E.; Fair, Ray C. (Prentice Hall, 1994)
Based on the belief that economics is a way of thinking, this text motivates students with clear explanations, good graphs, lively writing, and interesting and relevant examples. This edition features a logical organization of topics, an accessible presentation, and a hands- on focus to help students learn how to solve problems and think analytically. The abundance of real- world examples and coverage of current issues both show students how relevant economic concepts are to their lives and their world. A comprehensive, high-quality, ancillary package is available, providing all the tools necessary to encourage critical thinking.